Integrating Artificial Intelligence in Career Counseling based on Needs Assessment of Chinese Undergraduate Students - Zhou, Kangkang; Sriwisathiyakun, Kanyarat; Petsangsri, Sirirat (My University, 2025)
Purpose: This research focused on the needs of undergraduate students for effective career services in higher education institutes in Nanjing, China. Furthermore, the researcher also developed an AI Career Counseling Platform by integrating AI into a student career counseling service to meet the identified needs of students. Methods: This study consisted of two phases. In the first phase, a needs assessment survey was conducted to identify specific needs, preferences, and challenges of 384 undergraduate students selected by a multistage sampling method in Nanjing City, China. In phase two, the AI Career Counseling Platform was developed and subsequently evaluated by a panel of five experts. Results: Key findings from the needs assessment reveal three areas of particular importance to undergraduate students with a strong need for job-seeking counseling (mean score: 4.75), access to an alumni network (mean score: 4.84), and Entrepreneurship information (mean score: 4.72). Based on these insights, the platform Zhidada was developed. The expert panel further evaluated the platform, categorizing it as "Most Appropriate," with an average score of 4.75 for overall quality and technical development and a content suitability score of 4.74. Implications: This research significantly contributed to advancing the AI Career Counseling Platform by integrating students into career counseling services and expert insights, thus laying a strong foundation for enhancing career services in higher education.
Keywords: AI Career Service; Artificial Intelligence (AI); Career Counseling Platform; Job Seeking; Needs Assessment; Undergraduate Students